2013
DOI: 10.1186/1472-6785-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Objective sampling design in a highly heterogeneous landscape - characterizing environmental determinants of malaria vector distribution in French Guiana, in the Amazonian region

Abstract: BackgroundSampling design is a key issue when establishing species inventories and characterizing habitats within highly heterogeneous landscapes. Sampling efforts in such environments may be constrained and many field studies only rely on subjective and/or qualitative approaches to design collection strategy. The region of Cacao, in French Guiana, provides an excellent study site to understand the presence and abundance of Anopheles mosquitoes, their species dynamics and the transmission risk of malaria acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Our literature review shows that the specifics of sampling design are poorly reported and we therefore suggest that even when sampling is based on expert-opinion decisions, a full description of the sampling design should be provided to make the sampling repeatable or comparable or usable for subsequent similar studies. For example, field constraints such as presence of the disease or vector or host, vegetation type and density, elevation, field hostility, logistic feasibility, potential interference, human proximity, breeding sites, and risk of trapping material theft (13,20,21,24), which often are the major influence in the sampling design need to be declared and described. In fact, previous sampling campaigns are often used to inform future sampling design, and therefore standardization of sampling designs and protocols are now a priority (12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our literature review shows that the specifics of sampling design are poorly reported and we therefore suggest that even when sampling is based on expert-opinion decisions, a full description of the sampling design should be provided to make the sampling repeatable or comparable or usable for subsequent similar studies. For example, field constraints such as presence of the disease or vector or host, vegetation type and density, elevation, field hostility, logistic feasibility, potential interference, human proximity, breeding sites, and risk of trapping material theft (13,20,21,24), which often are the major influence in the sampling design need to be declared and described. In fact, previous sampling campaigns are often used to inform future sampling design, and therefore standardization of sampling designs and protocols are now a priority (12).…”
Section: Discussionmentioning
confidence: 99%
“…One method is to describe ecological strata in terms of transformed environmental variation (i.e. factorial analyses) (13), but the results can be difficult to interpret. By contrast, discriminant analysis (DA) requires less computational time and resources because no parameter tuning is required (54).…”
Section: Stratification (Ecological Delineation)mentioning
confidence: 99%
See 3 more Smart Citations